The Anglican Church in India - Cherian Thalakulam (Journal of Dharma, 1977)
It is paradoxical to note that many of the authentic books on Indian history are written by foreigners. These books, it should be admitted, are the results of deJigeni and painstaking research. There is no gainsaying that some of these books contain certain questionable points. This may be due to the prejudiced outlook of some authors who could not appreciate Indian culture. Consequently, they have sometimes disparaged the practices and customs of the natives. Such books should be taken with a pinch of salt. It is against this background that we have to evaluate the book of Miss Gibbs. One thing, very remarkable and noteworthy, is that she has skilfully avoided the above-mentioned pitfalls. Unlike many books, her book The Anglican Church in India 1600—1970 is very objective and frank. Her long stay in India has enabled her to assimilate and appreciate the Indian scene with all its divergences from the European civilization.